Biomechanics services: A question of co-operation - Schade, F. (New Studies in Athletics, 2010)
The interaction between a coach and a biomechanical diagnostician is a crucial element of developing a modern high-level athlete's performance. The aim of such co-operation should be to improve performance, but differences in approach, interests, understanding and technical terminology between the coach and diagnostician can complicate the process. Based on his experience working in the German federal sports system, the author explains that the role of the diagnostician is to provide an interface between science and practice. As such, the diagnostician cannot be fully in either camp but must be comfortable working in and speaking the language of both. He outlines the philosophy and the main areas of co-operation: 1) performance enhancement, 2) injury prevention and rehabilitation, 3) coaches education, stressing the importance of communication and need for diagnosticians to build teams within their fields of expertise and with experts from different fields, like physiology and psychology. He then presents examples of co-operation, highlighting the interaction between the coach and diagnostician. He concludes by stating that secrets for successful biomechanical services do not exist, it is all about face-to-face communication, work, dedication and sustainability.